ANALISIS DAMPAK PENGGUNAAN GADGET DALAM PENERAPAN KARAKTER PROFIL PELAJAR PANCASILA PADA SISWA SEKOLAH DASAR - Prasetyani, Kusumaningrum; Darmuki, Agus; W, Sri Surachmi; Ismaya, Erik Aditia Aditia (Universitas Muria Kudus, 2024)
This study aims to analyze the impact of gadget use in the application of the Pancasila Student Profile character of grade VI students of SDN 3 Pojok. The research method used is qualitative with a narrative approach. Data were collected through observation, interview, and documentation. The results showed that the use of gadgets can affect students' character development, both positively and negatively. Gadgets can be used as a useful tool in supporting the learning process, by using gadgets in learning students become more independent, critical reasoning and creative in learning. However, excessive and uncontrolled use can cause students to become less focused on learning, reduce social interaction, and reduce time that should be used for more useful activities. This can be seen in the decline in social attitudes, independence and caring attitudes in students. This research is expected to provide a deeper insight into how gadgets affect students' character development and how the role of parents and teachers in supervising the use of gadgets so that it still has a positive impact on students.